Reflexão sobre prevenção de acidentes à criança no âmbito doméstico - Bolsoni, Marília [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The aim was to reflect what action to prevent accidents used by caregivers / participants in the home. This is a prospecive cross-sectional descriptive study conducted at the Pediatric Inpatient Unit, Hospital of the Medical School of Botucatu – Unesp, during the months from May to August 2010.A questionnaire was used in the form of check list (Annex I) on measures to prevent accidents. The participant chose two alternatives taking into consideration the order of priority in the prevention of accidents. This study shows that for the age group from 29 days to 2 years, the companions chose these preventive measures for falls, burns, poisoning and drowning, “do not put near the windows mobile” (27.8%), “no access the match, lighter and appliances (22.2%), leave toxic substances out of reach and sight of children (41.7%) and empty buckets, tubs and pools after use (27.8% ). Regarding the age group 2-6 years, the measures for these types of accidents were not put near the windows mobile (26.5%), do not have access to matches, lighters and household appliances (20.9% ), leave toxic products out of reach and sight of children (27.9%) and maintain tanks, tanks and wells or struck with some protection (20.2%). For ages 6 to 10 years, the measures chosen to more such accidents were dry liquid spilled on the ground (23.5%), do not have access to matches, lighters and household appliances (22.5% ), leave toxic products out of reach and sight of children (31%) and keep tanks, tanks and wells or struck with some protection (23.5%). One fact that attracted our attention was that the preventive measures most frequently used by caregivers, regardless of age, show results that differ in few alternatives. It is essential to the understanding of the escorts / participants on the importance of injury prevention. Even today is predominantly defined as accident, injury must be addressed through measures

O objetivo do estudo foi refletir quais as medidas de prevenção de acidentes utilizadas pelos acompanhantes/participantes no âmbito doméstico. Trata-se de um estudo descritivo prospectivo transversal realizado na Unidade de Internação Pediátrica do Hospital das Clínicas da Faculdade de Medicina de Botucatu – Unesp, durante os meses de maio a agosto de 2010. Foi utilizado um questionário em forma de check list (Anexo I), sobre as medidas de prevenção de acidentes. O participante escolheu duas alternativas levando em consideração a ordem de prioridade na prevenção do acidente. O presente estudo mostra que para a faixa etária de 29 dias a 2 anos, os acompanhantes escolheram tais medidas preventivas para quedas, queimaduras, intoxicações e afogamento: “não colocar móvel próximo às janelas” (27,8%), “não ter acesso a fósforo, isqueiro e eletrodomésticos” (22,2%), “deixar substâncias tóxicas fora do alcance e da vista das crianças” (41,7%) e “esvaziar baldes, banheiras e piscinas após o uso” (27,8%). Com relação a faixa etária de 2 a 6 anos as medidas para tais tipos de acidentes foram: “não colocar móvel próximo às janelas” (26,5%), “não ter acesso a fósforo, isqueiro e eletrodomésticos” (20,9%), “deixar produtos tóxicos fora do alcance e da vista das crianças” (27,9%) e “manter cisternas, tonéis e poços trancados ou com alguma proteção” (20,2%). Para a faixa etária de 6 a 10 anos, as medidas mais escolhidas para esses acidentes foram: “secar substâncias líquidas derramadas no chão” (23,5%), “não ter acesso a fósforo, isqueiro e eletrodomésticos” (22,5%), “deixar produtos tóxicos fora do alcance e da vista das crianças” (31%) e “manter cisternas, tonéis e poços trancados ou com alguma proteção” (23,5%). Um dado que nos chama atenção foi que as medidas de prevenção mais utilizadas pelos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Acidentes infantis; Acidentes domésticos